2020
DOI: 10.1093/tas/txaa039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding liquid lactose or molasses to pelleted swine diets on pellet quality and pig performance

Abstract: Two experiments were conducted to evaluate the effects of including liquid lactose (LL) and molasses (M) in swine diets on pellet quality and pig performance. In experiment 1, a total of 194 nursery pigs (DNA 241 × 600, initially 6.7 ± 0.4 kg at 27 d of age) were used in a 33-d experiment evaluating the effects of LL (SweetLac 63; Westway Feed Products, Tomball, TX) or cane molasses on nursery pig performance and pellet quality. Pelleted experimental diets were fed from d 0 to 21, and a common pelleted diet fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It should also be kept in mind that the use of various milk by-products can be problematic due to their negative impact on pellet mill throughput. Appropriate combinations of diet moisture level, heat, and shear help to minimize their impact in this regard ( Dunmire et al, 2020 ). Increasing the level of fat in the diet by adding fat directly or utilizing basal ingredients with higher endogenous fat content is frequently recommended.…”
Section: Dietary Approaches To Improve Abf Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be kept in mind that the use of various milk by-products can be problematic due to their negative impact on pellet mill throughput. Appropriate combinations of diet moisture level, heat, and shear help to minimize their impact in this regard ( Dunmire et al, 2020 ). Increasing the level of fat in the diet by adding fat directly or utilizing basal ingredients with higher endogenous fat content is frequently recommended.…”
Section: Dietary Approaches To Improve Abf Productionmentioning
confidence: 99%
“…Furthermore, researchers have investigated alternative carbohydrates with interesting results. Dextrose, sucrose, liquid lactose and molasses have all been proposed as full or partial replacements for dried lactose ( Dunmire et al, 2020 ; Zhao et al, 2021 ). Recently, Clouard et al (2018) reported that using maltodextrin in place of lactose in a liquid milk replacer improved cognitive performance 8 wk later and did not impact growth performance.…”
Section: Dietary Approaches To Improve Abf Productionmentioning
confidence: 99%
“…Therefore, adding molasses in mixer or in a conditioner together with steam may aid compaction of particles during the pelleting process [ 52 ]. In the study by Dunmire [ 58 ], liquid sugar cane molasses was used as a substitute for whey permeate in nursery pig diets at a level of 9.4% significantly improved pellet durability and reduced amount of fines after the pelleting process. As far as the authors of this review are aware, there is no literature that investigates the influence of addition of soybean molasses in animal feed diets on the pelleting process and pellet quality.…”
Section: Soybean Molasses In Animal Feed Productionmentioning
confidence: 99%
“…Even so, soybean molasses is still a viscous and sticky liquid that must be uniformly added into the mixer during feed production by spraying through the nozzle. Otherwise, it can create lumps in mash feed which can negatively influence diet homogeneity or pellet quality, and it also requires frequent cleaning since it can create build-ups in mixer or pellet die and, therefore, increase wear of the equipment [ 58 ].…”
Section: Limitations Of Commercial Application Of Soybean Molassesmentioning
confidence: 99%